The Relationship Of The Family And The The Midwifer In Decision Making For Complicated Referrals Maternal In The Work Area Kuprik Health Center - Susana Sri Wahyuni; Asruria Sani Fajriah; Candra Wahyuni; Putri Eka Sejati (Journal of Health Science Community, 2024)
Maternal deaths are one of the causes of delays in making referral decisions. This study aims to determine the relationship between the role of the family and the role of midwives in decision making for referrals for maternal complications in the Kuprik Community Health Center working area.This research uses an analytical observational research design with a cross sectional approach. Using the accidental sampling technique, a sample of 30 respondents was obtained, the independent variable (family role and midwife’s role) and the dependent variable (referral decision making) using a questionnaire. The Chi-Square statistical test was used to determine the relationship between the two variables.The research results showed that the majority of respondents had families who did not play a role in making decisions regarding referrals for maternal complications, namely 17 respondents (56.7%), the majority of respondents had a role for midwives in making decisions regarding referrals for maternal complications, namely 27 respondents (90%) , and the majority of respondents refused to be referred, namely 16 respondents (53.3%).Chi-Square statistical test analysis found that there was a relationship between the role of the family in making decisions regarding referrals for maternal complications (p value = 0.000 < 0.05), and there was no relationship between the role of midwives in making decisions regarding referrals for maternal complications (p value = 0.088 > 0, 05).The need for a good family role in making decisions regarding referrals for maternal complications through the role of the husband, wife’s parents and in-laws. Apart from that, the midwife’s role in making decisions regarding referrals for maternal complications must be increased to the role of facilitator.